Limit

Calculus Level pending

lim x 0 + 0 arctan x sin ( t 2 ) d t x cos x x \large \lim_{x\to0^+} \dfrac{ \displaystyle \int_0^{\arctan x} \sin(t^2) \, dt}{x \cos x - x}

Find the value of the closed form of the above limit to 3 decimal places.


The answer is -0.667.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

It's known that the undefined integral of a integrable function is a continous function. So there's an indetermination, 0 0 \frac{0}{0} .

Applying L'Hopital:

lim x 0 + ( 0 a r c t a n ( x ) s i n ( t 2 ) d t ) ( x c o s ( x ) x ) = lim x 0 + s i n ( a r c t a n 2 ( x ) ) 1 1 + x 2 c o s ( x ) x s i n ( x ) 1 \huge\lim_{x \rightarrow 0^{+}}\frac{(\int_{0}^{arctan(x)}sin(t^2)dt)^{'}}{(xcos(x)-x)^{'}} = {\huge\lim_{x \rightarrow 0^{+}}\frac{ {sin(arctan^2(x))\frac{1}{1+x^2}}}{cos(x)-xsin(x)-1}}

= lim x 0 + s i n ( a r c t a n 2 ( x ) ) a r c t a n 2 ( x ) × a r c t a n 2 ( x ) x 2 × 1 1 + x 2 × x 2 c o s ( x ) x s i n ( x ) 1 {\huge=\lim_{x \rightarrow 0^{+}}\frac{{sin(arctan^2(x))}}{arctan^2(x)}\times\frac{arctan^2(x)}{x^2}\times\frac{1}{1+x^2}\times\frac{x^2}{cos(x)-xsin(x)-1}}

= lim x 0 + x 2 c o s ( x ) x s i n ( x ) 1 {\huge=\lim_{x \rightarrow 0^+}\frac{x^2}{cos(x)-xsin(x)-1}}

Applying L'Hopital again:

= lim x 0 + ( x 2 ) ( c o s ( x ) x s i n ( x ) 1 ) = lim x 0 + 2 x 2 s i n ( x ) x c o s ( x ) {\huge=\lim_{x \rightarrow 0^+}\frac{(x^2)^{'}}{(cos(x)-xsin(x)-1)^{'}} {\huge=\lim_{x \rightarrow 0^+}\frac{2x}{-2sin(x)-xcos(x)}}}

= lim x 0 + 2 2 s i n ( x ) x c o s ( x ) = 2 3 0.667 {\huge=\lim_{x \rightarrow 0^+}\frac{2}{-2\frac{sin(x)}{x}-cos(x)}=-\frac{2}{3}\approx-0.667}


( 0 a r c t a n ( x ) s i n ( t 2 ) d t ) (\int_{0}^{arctan(x)}sin(t^2)dt)^{'}

Let f ( x ) = 0 x s i n ( t 2 ) d t f(x)=\int_{0}^{x}sin(t^2)dt and g ( x ) = a r c t a n ( x ) g(x)=arctan(x)

f ( g ( x ) ) = 0 a r c t a n ( x ) s i n ( t 2 ) d t f(g(x))=\int_{0}^{arctan(x)}sin(t^2)dt

f ( g ( x ) ) = f ( g ( x ) ) × g ( x ) f(g(x))^{'}=f^{'}(g(x))\times g^{'}(x)

( 0 a r c t a n ( x ) s i n ( t 2 ) d t ) = f ( g ( x ) ) × g ( x ) = s i n ( a r c t a n 2 ( x ) ) × 1 1 + x 2 (\int_{0}^{arctan(x)}sin(t^2)dt)^{'}=f^{'}(g(x))\times g^{'}(x)=sin(arctan^2(x))\times\frac{1}{1+x^2}

What is sen(x).

Can u xplain the second step ?

Kushal Bose - 4 years, 4 months ago

Log in to reply

Sen(x) is how I write sin(x), i try to avoid it here but sometimes it happens, already edited, thanks.

Now the second step:

s i n ( a r c t a n 2 ( x ) ) 1 1 + x 2 c o s ( x ) x x s i n ( x ) 1 = s i n ( a r c t a n 2 ( x ) ) ( c o s ( x ) x x s i n ( x ) 1 ) ( 1 + x 2 ) = s i n ( a r c t a n 2 ( x ) ) ( a r c t a n 2 ( x ) ) ( c o s ( x ) x x s i n ( x ) 1 ) ( 1 + x 2 ) ( a r c t a n 2 ( x ) ) \frac{ {sin(arctan^2(x))\frac{1}{1+x^2}}}{cos(x)-x-xsin(x)-1}=\frac{ {sin(arctan^2(x))}}{(cos(x)-x-xsin(x)-1)(1+x^2)}=\frac{ {sin(arctan^2(x))(arctan^2(x))}}{(cos(x)-x-xsin(x)-1)(1+x^2)(arctan^2(x))}

As x 0 , a r c t a n 2 ( x ) 0 x \rightarrow 0 , arctan^2(x) \rightarrow 0 , so s i n ( a r c t a n 2 ( x ) ) a r c t a n 2 ( x ) = 1 \frac{sin(arctan^2(x))}{arctan^2(x)}=1

We are left with ( a r c t a n 2 ( x ) ) ( c o s ( x ) x x s i n ( x ) 1 ) ( 1 + x 2 ) \frac{ {(arctan^2(x))}}{(cos(x)-x-xsin(x)-1)(1+x^2)} and it's known that a r c t a n ( x ) x = 1 \frac{arctan(x)}{x}=1 as x 0 x \rightarrow 0 :

( a r c t a n 2 ( x ) ) x 2 ( c o s ( x ) x x s i n ( x ) 1 ) ( 1 + x 2 ) x 2 = 1 1 + x 2 ( a r c t a n ( x ) x ) 2 x 2 c o s ( x ) x x s i n ( x ) 1 \frac{ {(arctan^2(x))x^2}}{(cos(x)-x-xsin(x)-1)(1+x^2)x^2}=\frac{1}{1+x^2}(\frac{arctan(x)}{x})^2\frac{x^2}{cos(x)-x-xsin(x)-1}

When taking limits they'll all be one exept for the third fraction.

(I did this on my mobile phone, when i get home if you can't understand i'll do it more clearly on my computer)

Joao Miguel Coelho - 4 years, 4 months ago

Log in to reply

Differentiation of x c o s x x xcosx-x will be c o s x x s i n x 1 cosx-x sinx -1 but you have written something other.Can u recheck that ?

Kushal Bose - 4 years, 4 months ago

Log in to reply

@Kushal Bose Yes you are right, x -x was wrong there, but was just a typo because as you can see i didnt use it anywhere else

Joao Miguel Coelho - 4 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...